Alcohol and Tobacco Use in an Ethnically Diverse Sample of Breast Cancer Patients, Including Sea Island African Americans: Implications for Survivorship - Bea, Vivian J.; Cunningham, Joan E.; Alberg, Anthony J.; Burshell, Dana; Bauza, Colleen E.; Knight, Kendrea D.; Hazelton, Tonya R.; Varner, Heidi; Kramer, Rita; Bolick, Susan; Hurley, Deborah; Mosley, Catishia; et al. (Frontiers in Oncology, 2018)
Background/Objective: Data suggest that modifiable risk factors such as alcohol and tobacco use may increase the risk of breast cancer (BC) recurrence and reduce survival. Female BC mortality in South Carolina is 40% higher among African Americans (AAs) than European Americans (EAs). Given this substantial racial disparity, using a cross-sectional survey design we examined alcohol and tobacco use in an ethnically diverse statewide study of women with recently diagnosed invasive breast cancer. This included a unique South Carolina AA subpopulation, the Sea Islanders (SI), culturally isolated and with the lowest European American genetic admixture of any AA group. Methods: Participants (42 EAs, 66 non-SI AA, 29 SIs), diagnosed between August 2011 and December 2012, were identified through the South Carolina Central Cancer Registry and interviewed by telephone within 21 months of diagnosis. Self-reported educational status, alcohol consumption and tobacco use were obtained using elements of the Behavior and Risk Factor Surveillance System questionnaire. Results: Alcohol: EAs were approximately twice as likely to consume alcohol (40%) and to be moderate drinkers (29%) than either AA group (consumers: 24% of non-SI AAs, 21% of SIs; moderate drinkers 15% and 10% respectively). Users tended to be younger, significantly among EAs and non-SI AAs, but not SIs, and to have attained more education. Heavy drinking was rare (<=1%) and binge drinking uncommon (<=10%) with no differences by race/ethnicity. Among both AA subgroups but not EAs, alcohol users were six to nine times more likely to have late stage disease (Regional or Distant), statistically significant but with wide confidence intervals. Tobacco: Current cigarette smoking (daily or occasional) was reported by 14% of EAs, 14% of non-SI AAs and 7% of SIs. Smoking was inversely associated with educational attainment. Use of both alcohol and cigarettes was reported by 3 to 6% of cases. Conclusions: Prevalences of alcohol and cigarette use were similar to those in the general population, with alcohol consumption more common among EAs. Up to half of cases used alcohol and/or tobacco. Given the risks from alcohol for disease recurrence, and implications of smoking for various health outcomes, these utilization rates are of concern.